Extruded recycled plastic as a partial coarse aggregate in concrete - Costello, Lauren (Kansas State University, 2021)
Concrete usage has reached an all-time high and is only expected to continue to increase as population increased and more areas become industrialized. The natural resources used to make concrete are finite and the consumption of some resources, aggregates in particular, has surpassed the natural rate of renewal (Gu & Ozbakkaloglu, 2016). Replacement materials must be found if concrete is to continue to be used at increasing rates. A possible replacement material for aggregates is recycled plastic materials. This solution would also contribute to the removal of growing amount of plastic from the waste stream. This research examines the application of an extruded plastic replacement coarse aggregate product called Plazrok, developed by the company Enviroplaz. Fresh and hardened properties were observed and recorded of a control mix as well as a 15%, 30%, and 45% replacement rate by volume. The tests performed on the hardened concrete were compression, splitting tensile, and modulus of rupture. A significant change in fresh concrete properties did not occur. As the rate of replacement of the aggregate increased, a decrease in the compression, splitting tensile and modulus of rupture strength was observed. The compression tests give a proportional decrease in strength with the increase in replacement aggregate, 19.1%, 35.9% and 48.1% decrease in compressive strength at 15%, 30%, and 45% replacement, respectively. Equations to calculate the decrease in strength are presented. Tensile splitting and modulus of rupture show decreases in strength but not with the same consistency. Splitting tensile strength at 28-day strength decreased at most 21.9% but the seven-day strength showed the greatest decrease of 46.67%. The modulus of rupture at 28-day strength showed a 7.9%, 12.4%, and 28.5% decrease at 15%, 30%, and 45% replacement, respectively.
Keywords: Concrete; Alternative aggregate; Extruded plastic aggregate; Sustainability; Mechanical properties; Recycled plastic aggregate concrete